Perancangan Sistem Informasi Manajemen Penduduk Menggunakan Metode Agile Berbasis Website Pada Kantor Desa Batok Kecamatan Tenjo - Roswina, Rahmy; Harits, Abdurrahman (Journal of Information Systems and Business Technology, 2026)
The Batok Village Office in Tenjo District currently manages population data using a simple spreadsheet application, Microsoft Excel. The use of this manual system for data management creates various problems, including time-consuming data retrieval processes, the risk of errors in recording, duplicate data, and the potential for file loss. This study aims to replace the Microsoft Excel-based population data management system with a more efficient and integrated website-based system, design a population management information system that facilitates easy and accurate data recording, storage, retrieval, and reporting, implement a system with better data security to reduce the risk of data loss, and provide functional features such as automatic validation, fast search, and data backup to support the performance of village officials. The system development method used is the Agile method, which emphasizes iterative and incremental development processes and involves regular user feedback. The system was built using PHP and MySQL. Testing was conducted using the Black Box Testing method to ensure each function runs according to specifications. The results of the study indicate that the system is able to improve data management efficiency, minimize errors, speed up administrative services, and increase user satisfaction. Thus, this system can be an effective digital solution to improve the quality of public services at the village level.